Prevalence of Multivitamin Supplements useAmong General Population of Rawalpindiand Islamabad - Shahzad, Asima; Mashhadi, Syed Fawad; Safdar, Sarah; Sultan, Adil; Osama, Hassan; Ali Shah, Syed Maaz; Kashaf, Noor e; Abbas, Sana (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the prevalence of multivitamin supplement use among prescribed and non-prescribed population of Rawalpindi and Islamabad Pakistan.Study Design: It was a Quantitative analytical cross-sectional study.Place and Duration of Study: The study was carried out among general population of Rawalpindi and Islamabad Pakistan,from Jan till Apr 2022.Methodology: Nonprobability convenient sampling technique was used. The sample size was 385. The data was gathered through an online survey and was analyzed using IBM SPSS statistics version 25. Chi-square test was applied on qualitative variables with p-value significant at